The Diversity of the dragonfly (Odonata) as an indication of water quality - Muhammad Agus; Yulia Pujiastuti; Yuanita Windusari (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
Information on the diversity of dragonfly in the University area is still not much. Reduced areas that support the growth and development of dragonfly species are thought to have an impact on the decline of the population and the diversity of these species. The purpose of this study identified and analyzed the diversity of dragonfly species. Dragonfly are collected through direct capture and using sticky traps, then visual observations are made for identification. Environmental conditions in the area of Sriwijaya University Campus is still good, with the visibility of environmental parameters in the form of DO, BOD and COD still meet environmental quality standards so that dragonflies are still able to lay eggs to keep their generation. Sriwijaya University campus found 19 species of Odonata belonging to 5 families and 2 sub-ordo, with the value of species diversity index of 2.05 and moderate